2004
DOI: 10.1177/010740830402400406
|View full text |Cite
|
Sign up to set email alerts
|

Informal Home Caregiving in a Gender Perspective: A Selected Literature Review

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(42 reference statements)
0
6
0
2
Order By: Relevance
“…Though an earlier body of literature documented that, compared to women caregivers, men faced lower levels of depression, strain, and psychological distress, other studies have disputed these findings [26,27,28,29]. Men may underreport the level of burden they experience because they are less likely to admit their negative feelings [26,30] or less in tune with how to process and share emotions [28,29,31], because existing burden instruments may not accurately speak to men’s experiences of burden [11], or because acknowledgment of burden could be culturally unacceptable [16]. Regardless of whether the literature favors one side or the other, or if men downplay their burden when answering these surveys, they do experience caregiver burden and self-esteem issues [30,32,33]: 62% reported moderate to very stressful caregiving experience and 46% moderate to severe physical strain [3].…”
Section: Introduction and Background Literaturementioning
confidence: 99%
“…Though an earlier body of literature documented that, compared to women caregivers, men faced lower levels of depression, strain, and psychological distress, other studies have disputed these findings [26,27,28,29]. Men may underreport the level of burden they experience because they are less likely to admit their negative feelings [26,30] or less in tune with how to process and share emotions [28,29,31], because existing burden instruments may not accurately speak to men’s experiences of burden [11], or because acknowledgment of burden could be culturally unacceptable [16]. Regardless of whether the literature favors one side or the other, or if men downplay their burden when answering these surveys, they do experience caregiver burden and self-esteem issues [30,32,33]: 62% reported moderate to very stressful caregiving experience and 46% moderate to severe physical strain [3].…”
Section: Introduction and Background Literaturementioning
confidence: 99%
“…Studies by Lindquist et al (2004) and Jacobi et al (2003) showed that caregiving influences the caregiver's options to do other activities and may give the helper as the feeling of being tied down. Several studies point out the importance of help, both from the public sector as well as informal help, to avoid carers feeling solely responsible for the person needing care (Stoltz et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Informal health-care is usually performed by someone in the family and mostly by women (8,17). Since the caring role can be experienced differently by men and women when it comes to workload, it is important to consider this when planning needs of support from the community (14,18).…”
Section: Discussionmentioning
confidence: 99%